Opening the doors for school health—An exploration of public health nurses' capacities to engage in comprehensive school health programs. Issue 3 (18th March 2019) - Sanders, Tanya; O'Mahony, Joyce; Duncan, Susan; Mahara, Star; Pitman, Valerie; Ringstad, Kristin; Weatherman, Kristine
Abstract: Objectives: Public health nurses (PHNs) have a significant role in engaging the voice and actions of school communities in promoting the health of children and youth. School nursing was one of the early 20th century public health nursing foci and specialties in Canada, however over several decades, there has been a gap in actualizing PHNs' full potential in schools. At the same time, intersectoral and interdisciplinary comprehensive school health (CSH) models have emerged as exemplars of partnerships between schools and communities to advance health promotion and ultimately chronic disease prevention with school populations (Pan‐Canadian Joint Consortium for School Health, 2018 ; World Health Organization, 2017 ). Design and Measurement: Using a participatory action research methodology we explored the role of PHNs in CSH, drawing on the concept of engagement in intersectoral healthy school teams. Results and Conclusions: The three themes that emerged from the data analysis were: facilitators of public health nursing engagement, barriers to public health nursing engagement, and the influences of community context on engagement. Overall, findings indicate that the PHN role in CSH must be developed and supported so that PHNs remain a vital link between school health communities, programs, and policies in the promotion of health.